The effect of Garcinia mangostana L. skin decoct exposure on Zebrafish embryo Danio rerio (Hamilton, 1822) - Yunita, Neri; Retnoaji, Bambang (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
Hypertension is one of the diseases with the highest prevalence in Indonesia and is the main cause of death in patients. Pregnant women have a risk of losing their baby due to hypertension or death. ACEI and ARB-type antihypertensive drugs are dangerous for pregnant women because they can cause fetal death. In ancient times, Indonesians have used plants as herbal medicines for generations. One of the plants that has medicinal properties is mangosteen skin (Garcinia mangostana L.) as an antihypertensive drug through its diuretic effects. However, the drugs consumed can have toxic effects if used in high concentrations. A teratogenic test is a toxic test that is specifically carried out to determine the presence of organ abnormalities in the fetus due to exposure to xenobiotic compounds. The zebrafish (Danio rerio) embryo was chosen as the research object because the chorion in the embryonic phase is transparent, so it is easy to observe. This study aimed to determine the effect of exposure to mangosteen rind decoction on zebrafish embryos' hatchability and spinal curvature. Observations were made using a Leica microscope with ANOVA data analysis. The observations showed that high treatment concentrations decreased heart rate, while high concentrations didn’t affect egg hatching rate, spine curvature, or pigment density.